The Influence of Transformational Leadership on Employee Performance at Ampeldento Village Office, Malang Regency - Korlina Kedu; Nur Ida Iriani; Warter Agustim; M. Rifa'i (International Journal of Management and Business, 2026)
The purpose of this research is to determine the effect of transformational leadership on employee performance at the Ampeldento Village Office in Malang Regency. The research conducted is quantitative in nature. The sampling method used in this study is total sampling, resulting in a sample size of 32 respondents. The data collection technique used by the researcher is a questionnaire. The data analysis method applied is simple linear regression using SPSS version 26. The results of the study prove that transformational leadership has a significant effect on employee performance at the Ampeldento Village Office in Malang Regency, as indicated by a t-value of 4.168, which represents an influence of 64.9%. Transformational leadership influences employee performance through motivation, a clear vision, and mission.